(untitled) (Journal of Fiber Bioengineering and Informatics, 2012)
The extracellular cellulase enzyme produced by Trichoderma reesei was used to prepare Nanocrystalline Cellulose (NCC) by controlled hydrolysis of bamboo fibers. The morphology of the prepared bamboo cellulose nanocrystals was characterized by field emission scanning electron microscopy and the crystallinity was measured by X-ray diffraction. The degree of polymerization was tested by automatic viscosimeter. The surface charge in suspension was estimated by Zeta-potential. The results showed that all NCC from bamboo fibers presented a rod-like shape, an average diameter of 24.7 nm and length of 286 nm, with an aspect ratio of around 12. The zeta potential of cellulase hydrolyzed NCC was 4 times lower than that of NCC prepared by acid hydrolysis process.